Rosemary Diterpenes and Flavanone Aglycones Provide Improved Genoprotection against UV-Induced DNA Damage in a Human Skin Cell Model - Noelia Sánchez-Marzo; Almudena Pérez-Sánchez; Enrique Barrajón-Catalán; Julián Castillo; María Herranz-López; Vicente Micol (MDPI AG, 2020)
Overexposure to solar ultraviolet (UV) radiation is the major cause of a variety of cutaneous disorders, including sunburn, photoaging, and skin cancers. UVB radiation (290−320 nm) causes multiple forms of DNA damage, p53 induction, protein and lipid oxidation, and the generation of harmful reactive oxygen species (ROS). In recent years, botanicals containing polyphenols with antioxidant and anti-inflammatory properties as skin photoprotective agents have emerged. This study evaluated the protective effects of two formulations against UVB-induced damage in a skin cell model. One of the formulations (F2) contained a combination of citrus and olive extracts and the other one (F1) also contained a rosemary extract. The antioxidant capacity of both formulations was estimated by different in vitro methods, and the cell viability, intracellular ROS generation, mitochondrial depolarization, and DNA damage were studied in UVB-irradiated human keratinocytes. Both formulations exerted photoprotective effects on skin cells and decreased mitochondrial depolarization and DNA damage. F1 which contained iridoids, rosemary diterpenes, glycosides and aglycones of citrus flavanones, and monohydroxylated flavones exhibited higher cellular photoprotective effects and mitochondrial membrane potential restoration, as well as an enhanced capacity to decrease DNA double strand breaks and the DNA damage response. In contrast, F2, which contained mostly iridoids, citrus flavanone aglycones, and mono- and dihydroxylated flavones, exhibited a higher capacity to decrease intracellular ROS generation and radical scavenging capacity related to metal ion chelation. Both formulations showed a similar capability to decrease the number of apoptotic cells upon UVB radiation. Based on our results and those of others, we postulate that the stronger capacity of F1 to protect against UVB-induced DNA damage in human keratinocytes is related to the presence of rosemary diterpenes and citrus flavanone aglycones. Nevertheless, the presence of the dihydroxylated flavones in F2 may contribute to inhibiting the generation of metal-related free radicals. To confirm the efficacy of these formulations as potential candidates for oral/topical photoprotection, human trials are required to circumvent the limitations of the cellular model.